The State of the Immune System in Сhildren with Bronchial Asthma who are at the Stage of Balneological Rehabilitation - N. N. Kaladze; A. I. Ezernitskaya; M. L. Babak (Детские инфекции (Москва))
Decrease in a-interferon (IFN-a) levels by 6.8% (p > 0.05) compared to the control group, IFN-g by 37.7% (p < 0.05), relative quantity of CD8 + lymphocytes — by 12.26% (p < 0.001) and an increase in the relative amount of CD4 + lymphocytes by 3.9% and CD95 + lymphocytes by 49.73% (p < 0.01), IgE levels 4.1 — fold (p < 0.001) and IL-4 — on 30% it was revealed in 36 children with bronchial asthma, who came to sanatorium-and-spa treatment. An increase in IFN-a levels by 74.7% (p < 0.01) compared with baseline, IFN-g 2.1 — fold (p < 0.001), relative CD8 + lymphocyte count — by 12.26% (p < 0.001) and a significant decrease in the relative amount of CD4 + lymphocytes — by 4.8% (p < 0.05) and CD95 + lymphocytes — by 23.84% (p < 0.01), IgE levels by 28.1% (p < 0.01) and IL-4 — 2.3 times observed after the using a drug containing a2b-interferon and antioxidants vitamins E and C — VIFERON® in the process of balneological treatment.